Neonatal and Maternal Outcomes With Prolonged Second Stage of Labor. Issue 2 (June 2015) - Laughon, S.K.; Berghella, V.; Reddy, U.M.; Sundaram, R.; Lu, Z.; Hoffman, M.K.
<x xml:space="preserve">Abstract</x> (Obstet Gynecol. 2014;124(1):57–67)